Nurses' competency in drawing blood cultures and educational intervention to reduce the contamination rate - Arif Al-Hamad; Maha Al-Ibrahim; Eman Alhajhouj; Waseelah Al-Alshaikh Jaffer; Jaffar Altowaileb; Hassan Alfaraj (Elsevier, 2016)
Summary: Compared with truly negative cultures, false positive blood cultures (BCs) not only increase laboratory work but also prolong the lengths of patient stays, which are likely to increase patient morbidity and costs. The present study aimed to evaluate the effectiveness of a hospital-wide educational intervention on BC contamination rates. Nurses performed all phlebotomies; therefore, educational workshops were offered to all nurses twice a week over a 3-month period. The workshops consisted of a questionnaire, PowerPoint presentation, video show, demonstration of the different materials used to collect BCs, and question session. Data from the questionnaires and laboratory culture results were compared between the 6-month pre- and post-intervention periods. Of the 503 eligible nurses, 216 (42.9%) attended the workshops. The survey identified areas for improvement, which included time of disinfectant application, volume of blood to be cultured, and disinfection of BC bottle tops. Of the 9903 BC sets that were drawn from 3649 patients during the study period, 676 (6.8%) were contaminated. The monthly BC contamination rates for the 6-month pre- and post-intervention periods were 8.1% and 5.2%, respectively, representing a 36% reduction (P = 0.008). Only three wards had an acceptable contamination rate of ≤3% before the intervention, compared with eight wards after the intervention. While contamination of BCs can never be completely eliminated, there is evidence that adherence to best practice BC collection techniques can minimize BC contamination, which might be best achieved with a dedicated phlebotomy team. Keywords: Pseudobacteremia, Aseptic technique, Phlebotomy team